ACTIVITY COMPONENT IN THE READYNESS STRUCTURE OF YOUNG TEACHER TO INNOVATIVE ACTIVITY in SYSTEMS OF METHODICAL WORK OF SCHOOL - I. Voloshchuk (Academy of Cognitive and Natural Sciences, 2008)
The article considers the specificity of formation the component of activity in the conditions of préparation of the young specialist to the introduction of innovations in the system of the school methodical work.